INVENTORY OF MEDICINAL PLANT IN THE REHABILITATION ZONE OF THE BLOK PASIR BATANG GUNUNG CIREMAI NATIONAL PARK - Nina Herlina; Ika Karyaningsih; Agus Yadi Ismail; Idit Sukmadi (Journal of Forestry And Environment, 2018)
The potential of plant diversity in the forest which has medicinal properties is still largely ignored and has not been utilized and developed. One of them is the potential that has not been identified regarding the existence of medicinal plants in the rehabilitation zone of Blok Pasir Batang. The aim of the study was to identify the potential of medicinal plant species and their efficacy in the Blok Pasir Batang  rehabilitation zone. The information produced is the result of scientific documentation collected as the initial data base in the rehabilitation zone.